The Influence of Digital Leadership and Academic Supervision on Learning Quality through Teacher Efficacy at SMP IT Daarul Hikmah Bontang - Shidiq, Ahmad Fajar; Hiyang, Anastasia; Musdalifah, Musdalifah; Nurlaili, Nurlaili; Ulfah, Jumiati; Haeruddin, Haeruddin (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Abstract This study aims to analyze the influence of digital leadership and academic supervision on the quality of learning mediated by teacher efficacy at SMP IT Bontang. The quality of learning in the digital era is key, and the role of leadership and teacher mentoring are essential factors. This study uses a quantitative approach with a survey method. The population in this study is all active teachers at SMP IT Daarul Hikmah Bontang, and using a saturated sampling technique, all 42 teachers were made respondents. The data analysis technique used was path analysis with the help of SPSS software. The results showed that (1) digital leadership had a positive and significant effect on teacher efficacy; (2) academic supervision had a positive and significant effect on teacher efficacy; (3) digital leadership, academic supervision, and teacher efficacy together had a significant effect on learning quality. These findings confirm that improving learning quality can be achieved effectively by strengthening digital leadership and academic supervision, which can enhance teacher efficacy. Keywords: academic supervision, digital leadership, integrated Islamic schools, learning quality, teacher efficacy Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh kepemimpinan digital dan supervisi akademik terhadap mutu pembelajaran yang dimediasi oleh efikasi guru di SMP IT Bontang. Kualitas pembelajaran di era digital menjadi kunci, dan peran kepemimpinan serta pendampingan guru menjadi faktor esensial. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi dalam penelitian ini adalah seluruh guru aktif di SMP IT Daarul Hikmah Bontang, dan dengan menggunakan teknik sampel jenuh, keseluruhan 42 guru dijadikan responden. Teknik analisis data yang digunakan adalah analisis jalur (path analysis) dengan bantuan perangkat lunak SPSS. Hasil penelitian menunjukkan bahwa (1) kepemimpinan digital berpengaruh positif dan signifikan terhadap efikasi guru; (2) supervisi akademik berpengaruh positif dan signifikan terhadap efikasi guru; (3) kepemimpinan digital, supervisi akademik, dan efikasi guru secara bersama-sama berpengaruh signifikan terhadap mutu pembelajaran. Temuan ini menegaskan bahwa peningkatan mutu pembelajaran dapat dicapai secara efektif melalui penguatan kepemimpinan digital dan supervisi akademik yang mampu meningkatkan efikasi guru. Kata kunci: efikasi guru, kepemimpinan digital, mutu pembelajaran, sekolah Islam terpadu, supervisi akademik,